2020
DOI: 10.1073/pnas.1914713117
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopy through a plasmonic nanolens

Abstract: Plasmonics now delivers sensors capable of detecting single molecules. The emission enhancements and nanometer-scale optical confinement achieved by these metallic nanostructures vastly increase spectroscopic sensitivity, enabling real-time tracking. However, the interaction of light with such nanostructures typically loses all information about the spatial location of molecules within a plasmonic hot spot. Here, we show that ultrathin plasmonic nanogaps support complete mode sets which strongly influence the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…The collection C s = 0.67 comes from Lambertian emission with 5% losses and the solid angle restricted by total internal reflection at the glass–air interface, while C N = 0.55 is given by the predominantly high angle emission of the NPoM collected by the same NA = 0.9 objective. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection C s = 0.67 comes from Lambertian emission with 5% losses and the solid angle restricted by total internal reflection at the glass–air interface, while C N = 0.55 is given by the predominantly high angle emission of the NPoM collected by the same NA = 0.9 objective. 44 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…The ratio between experiments and simulations can be accounted for by less controlled experimental parameters such as in-/out-coupling efficiencies of the NPoM, orientation, and spatial distribution of molecules in the gap. 44 …”
Section: Resultsmentioning
confidence: 99%
“…We assemble NPoM [ 23,27–29 ] constructs (Figure 1a) using deoxyribonucleic‐acid origami (DNAo) technology and extend it to place individual molecules at the sites of interest. As previously demonstrated, [ 23,30 ] DNAo is a powerful tool to reliably and consistently construct such architectures.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to notice that the simulated EF of 10 6 is not sufficient to observe single‐molecule SERS and that greater than 90% of the EM field in the gap is polarized along the z ‐direction normal to the metal facets. [ 29,39 ]…”
Section: Resultsmentioning
confidence: 99%
“…In the context of faithful super-resolution microscopy on particles, the problem has been studied by coupling emitters to silver and gold spheres, 18 , 21 , 22 triangles, 19 nanorods, 16 , 20 , 27 nanoislands, 18 , 28 nanowires, 15 , 17 , 29 31 and particle-on-film systems. 32 The modification of the PSF has further been explored from a theoretical point of view by using analytical approximations 33 or numerical simulations for spheres, 34 nanorods, 16 and triangles. 19 In some studies mislocalization was observed as a dominant effect, 16 , 18 22 other studies reported it to be negligible compared to the localization precision of the microscope, 4 , 35 and some studies reported exotic multilobed PSFs.…”
Section: Introductionmentioning
confidence: 99%